2021
DOI: 10.1158/2159-8290.cd-20-1741
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Activation of p53 Triggers Viral Mimicry Response Thereby Abolishing Tumor Immune Evasion and Promoting Antitumor Immunity

Abstract: The repression of repetitive elements is an important facet of p53's function as a guardian of the genome. Paradoxically, we found that p53 activated by MDM2 inhibitors induced the expression of endogenous retroviruses (ERVs) via increased occupancy on ERV promoters and inhibition of two major ERV repressors, histone demethylase LSD1 and DNA methyltransferase DNMT1. Double-stranded RNA stress caused by ERVs triggered type I/III interferons expression and antigen processing and presentation. Pharmacological act… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 53 publications
0
85
0
Order By: Relevance
“…Tumours immunologically classified as intermediate showed enrichment of TP53 mutations and losses in genes related to antigen presentation and interferon signalling. Interestingly, loss of TP53 in cancer cells promotes the recruitment of immune suppressive cells and attenuates the response of both cytotoxic and T-helper cells 43 44. Therefore, the increased rate of TP53 mutations seen in the intermediate class could be key in promoting an immunosuppressive microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Tumours immunologically classified as intermediate showed enrichment of TP53 mutations and losses in genes related to antigen presentation and interferon signalling. Interestingly, loss of TP53 in cancer cells promotes the recruitment of immune suppressive cells and attenuates the response of both cytotoxic and T-helper cells 43 44. Therefore, the increased rate of TP53 mutations seen in the intermediate class could be key in promoting an immunosuppressive microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…GC patients with wild type TP53 generally have plentiful intratumoral lymphocyte infiltration [28] , which is associated with favorable prognosis and increased ICIs sensitivity. Recently, an in vivo study further corroborated that the TP53 is a favorable condition for T cell infiltration and checkpoint therapy [29] . Likewise, the present study also observed an improved survival trend in patients with wild-type TP53 status, and the potential high mutation rate and TILs in MSS/TP53+ might be the underlying mechanisms for improved survival and further suggest the rationality of ICIs therapy in appropriated HAS patients.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, it can be said that the presence of migrating metastatic cancer cells may stimulate immune response within the human body [ 95 , 96 , 97 ]. The biomarkers present on these migrating cancer cells can be recognised by the immune cells and eventually trigger the immune system to produce antibodies to neutralise the expression of the biomarkers [ 95 , 98 ]. The crosstalk between cancer and immune cells contributes to another layer of complexity to our understanding of the formation of metastasis, but at the same time opens new therapeutic opportunities for patients such as cancer immunotherapy [ 96 , 99 ].…”
Section: The Connection Between Breast Cancer and The Immune Systemmentioning
confidence: 99%